Attachment to God dan gratitude pada mahasiswa universitas ‘x’ Bandung - Satyawan, Lisa Imelia; Kiswantomo, Heliany (Universitas Muhammadiyah Surakarta, 2020)
Abstract. This study was conducted to measure correlation between attachment to God and students’ gratitude in “X” University. Gratitude is an appreciation of individual being grateful because he has received kindness form others. Grateful people will be healthier, more enthusiastic, and optimistic. One of the factors that influences the development of gratitude is spiritual life or religiosity, which reflects human view of God, known as attachment to God. The hypothesis was there was a correlation between attachment to God and gratitude. This was a correlational research design, with 100 students of University “X” as participants. The instruments were questionnaire of gratitude and attachment to God. Data were analyzed using Chi Square. The result revealed that there was no correlation between attachment to God and gratitude. Attachment to God’s dimensions did not have any correlation with gratitude too. This study also revealed that age and gender show no relationship tendencies with gratitude. For further research, next researchers are suggested to measure correlation between gratitude and other factors.Keywords: attachment to God; dimension of attachment to God; gratitude